Digital Interpreting Tools as A New Perspective for Cultural and Natural Tourist Routes - Tomasz DUDA (Communications of International Proceedings, 2021)
In tourism, digital interpretation tools, mobile applications and virtual tour guiding have determined the contemporary tourist space in the past several years. The phenomenon has been observed not only in urban, active and special interest tourism, but also cultural and natural tourism which are based on the direct contact between the tourist and the surrounding environment. Cultural and natural-cultural theme routes form an integral part of the cultural tourism space. These routes promote intensive exchange of thought, information and activities while preserving cohesion, as well as thematic and organizational unity of the route. Due to the global rapid development of new technologies, as well as relatively common and affordable access to them, digital communication tools have become an indispensable element of tour guide narration and interpretation of tourist destinations. The development of versatile applications and specialist virtual reality programs give raise to questions about the future of tourism. Are we progressing toward virtual tourism and digital perception of space? As long as tourism involves emotions and individual experience, which so much rely on “analogue” factors, the digitalization of interpretation should remain at the information and organization levels, while keeping a reasonable balance between physical and virtual reality.
Keywords: Interpreting Cultural Heritage; Digital Tourism; Virtual Reality; Guiding; Tourist Routes